Large‐scale mortality in cultured tilapia Oreochromis niloticus due to infection with Shewanella putrefaciens in India. Issue 2 (10th February 2020) - Sood, Neeraj; Pradhan, Pravata K.; Ravindra,; Verma, Dev K.; Yadav, Manoj K.; Mishra, Rupesh K.; Kumar, Uday; Swaminathan, Thanga R.; Sood, Naresh K.
Abstract: In recent years, infection with Shewanella putrefaciens has emerged as a serious problem in freshwater aquaculture. In the present study, we report large‐scale mortality in farmed tilapia Oreochromis niloticus from Hisar, North India. The diseased tilapia exhibited lethargy, swimming near the water surface, fin rot, hemorrhages on the operculum, and approximately 40% mortality. Gram‐negative, motile, catalase, and oxidase‐positive bacilli were isolated from the kidney of affected tilapia and confirmed as S. putrefaciens on the basis of biochemical tests and 16S rRNA gene sequencing. The antimicrobial sensitivity test revealed that S. putrefaciens strains were sensitive to quinolone, nitrofuran, tetracycline, aminoglycoside, cephalosporin, aminocyclitol, sulphonamide, and macrolide antibiotics, but resistant to beta‐lactam and glycopeptide antibiotics. The histopathological examination revealed degenerative changes in the kidney, liver, spleen, and intestine suggesting systemic infection. In experimental infection studies, the disease was reproduced in naive tilapia, and the clinical signs resembled those observed in natural cases. Further more, S. putrefaciens was re‐isolated from the kidney of challenged tilapia, fulfilling Koch's postulates. Therefore, the mortality in tilapia was attributed to S. putrefaciens infection.